New insights in Type I and II CD20 antibody mechanisms‐of‐action with a panel of novel CD20 antibodies. (22nd February 2018) - Meyer, Saskia; Evers, Mitchell; Jansen, Johannes H. M.; Buijs, Jos; Broek, Blanca; Reitsma, Stephanie E.; Moerer, Petra; Amini, Mojtaba; Kretschmer, Anna; ten Broeke, Toine; den Hartog, Marcel T.; Rijke, Mark; et al.
Summary: Based on their mechanisms‐of‐action, CD20 monoclonal antibodies (mAbs) are grouped into Type I [complement‐dependent cytotoxicity (CDC) and antibody‐dependent cell‐mediated cytotoxicity (ADCC)] and Type II [programmed cell death (PCD) and ADCC] mAbs. We generated 17 new hybridomas producing CD20 mAbs of different isotypes and determined unique heavy and light chain sequence pairs for 13 of them. We studied their epitope binding, binding kinetics and structural properties and investigated their predictive value for effector functions, i.e. PCD, CDC and ADCC. Peptide mapping and CD20 mutant screens revealed that 10 out of these 11 new mAbs have an overlapping epitope with the prototypic Type I mAb rituximab, albeit that distinct amino acids of the CD20 molecule contributed differently. Binding kinetics did not correlate with the striking differences in CDC activity among the mIgG2c mAbs. Interestingly, chimerization of mAb m1 resulted in a mAb displaying both Type I and II characteristics. PCD induction was lost upon introduction of a mutation in the framework of the heavy chain affecting the elbow angle, supporting that structural changes within this region can affect functional activities of CD20 mAbs. Together, these new CD20 mAbs provide further insights in the properties dictating the functional efficacy of CD20 mAbs.